DESIGN AND COMPARISON OF U - SLOT MICRO STRIP ANTENNAS WITH DIFFERENT SLOT WIDTHS (Global Journals of Research in Engineering, 2011)
A Abstract -This paper presents design and comparison of two U slot microstrip antennas of different dimensions fed by a coaxial probe A coaxial feed microstrip antenna is proposed for linear polarization These antennas are implemented on glass epoxy dielectric substrate with r 4 4 h 1 6mm and resonant at 2 GHz The simulations are carried out using Zeland IE3D software
Keywords: U slot MSA; Micro strip; patch antenna; VSWR; IE3D